Experimental investigation of plastic waste pyrolysis fuel and diesel blends combustion and its flue gas emission analysis in a 5 kW heater. (15th May 2022) - Wang, Shuang; Rodriguez Alejandro, David Aaron; Kim, Hana; Kim, Jae-Young; Lee, Yu-Ri; Nabgan, Walid; Hwang, Byung Wook; Lee, Doyeon; Nam, Hyungseok; Ryu, Ho-Jung
Abstract: Environmental issues have become prominent due to an increase in the plastic wastes, which can be recyclable for an alternative liquid fuel. In this work, the upgraded plastic pyrolysis oil was used to investigate the combustion performance of the 5 kW scale heater. The plastic pyrolysis middle oil (diesel-like fraction, C11 –C22 ) was similar to the properties of the diesel (45.0 MJ/kg and 2.70 cSt). The plastic pyrolysis fuel and diesel blends were prepared. The efficiency of combustion using 10% and 30% pyrolysis fuel blends showed about 58% at a fuel-air equivalence ratio (Ф) of 0.91, which was similar to that of diesel combustion. The highest heater internal temperature was observed to be about 1060 °C (Ф = 0.91). In addition, the flue gas composition of all the blends showed similar concentrations of CO (∼13 ppm) and CO2 (∼13 vol%). However, a higher NOx concentration was observed with pyrolysis fuel blends (80–130 ppm) than that of diesel due to its higher nitrogen content in plastic waste pyrolysis fuel. Exergoeconomic analysis was also conducted to investigate the plastic pyrolysis fuel efficiency for more evaluation. This study suggested that plastic pyrolysis fuel has a good application prospects as an alternative fuel. Graphical abstract: Image 1 Highlights: P-fuel/diesel blends showed good miscibility, showing similar properties of diesel. The combustion efficiency of a 5 kW boiler was about 58% with the p-fuel blends. Three blends and diesel had similar concentrations of CO (∼13 ppm) and CO2 (∼13%). Higher NOx emission (60–130 ppm) was observed with pyrolysis fuel blends. Exergoeconomic analysis was conducted to evaluate the values of pyrolysis fuel.